2006
DOI: 10.1002/jsfa.2437
|View full text |Cite
|
Sign up to set email alerts
|

The effect of harvest date on the yield and mineral content of Phalaris arundinacea L. (reed canary grass) genotypes screened for their potential as energy crops in southern England

Abstract: The effect of harvest date on dry matter production per hectare and moisture content of 13 genotypes of Phalaris arundinacea (reed canary grass) was studied between 1995 and 1998 and N, P and K concentration in biomass was measured in 1998. There were two winter harvests, the first at crop senescence and the second after a subsequent delay of several weeks which varied each year. Average dry matter production was higher at the first (conventional) harvest than at the delayed harvest except in 1996. Each year t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 13 publications
9
48
0
3
Order By: Relevance
“…2) out of a total of 80 cultivars and accessions. These results are similar to results from a group of Canadian accessions [18], a group of Swedish accessions [12], and a group of continental European accessions evaluated in England [9].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2) out of a total of 80 cultivars and accessions. These results are similar to results from a group of Canadian accessions [18], a group of Swedish accessions [12], and a group of continental European accessions evaluated in England [9].…”
Section: Resultssupporting
confidence: 92%
“…Broad-sense heritability of biomass yield was 0.67, and the genotypic variance component was higher than all other variance components, except for the error variance. Although there was some significant genotype× environment interaction for biomass yield, these components made up only a small portion of the variance of a genotype (accession or cultivar) mean (15.8%), similar to observations made on other studies [2,9]. The consistent performance of populations across multiple locations and years reflects the broad adaptation of reed canary grass across the temperate North American landscape, resulting in fairly consistent genotypic expression for biomass yield at the sites chosen for this study.…”
Section: Resultssupporting
confidence: 66%
“…Finally, delayed harvest studies often cite nutrient changes on a total standing crop basis. It is perhaps more likely that overwinter physical changes such as leaf drop are influencing the change in mineral nutrient content from the fall to the spring [12,54]. Attempts to quantify these nutrient loss processes are worthy avenues of future research.…”
Section: Other Factors Affecting End-season Nutrient Lossmentioning
confidence: 99%
“…In the case of agricultural residues from some industrial processes; the amount of shells, husks and pits and the way in which the crops are processed also influence their composition [4]. Work on energy crop agronomy has shown that inorganics can also vary with fertilizer treatment and time of harvest, as well as the part of the biomass (leaf, stem etc) [5][6][7][8][9][10].…”
Section: Biomass Compositionmentioning
confidence: 99%